2007
DOI: 10.1007/s00240-007-0124-2
|View full text |Cite
|
Sign up to set email alerts
|

Tissue reactions of suture materials (polyglactine 910, chromed catgut and polydioxanone) on rat bladder wall and their role in bladder stone formation

Abstract: Suture materials are widely used in urological surgery especially in regions that are in contact with urine. In this study, we aimed to compare polyglactine 910, chromed catgut and polydioxanone sutures according to stone formation and inflammation, congestion and foreign body reaction that occur on bladder mucosa. Cystotomy procedure was performed, in three groups of Wistar female rats, with 4/0 polyglactine 910, 4/0 chromed catgut and 4/0 polydioxanone sutures. All groups were divided into two sub-groups wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 18 publications
2
26
0
Order By: Relevance
“…This might be due to the fact that it was the only braided type of suture evaluated, which could therefore have induced a more pronounced inflammation process. This also corresponds with other studies [24,25]. …”
Section: Discussionmentioning
confidence: 50%
“…This might be due to the fact that it was the only braided type of suture evaluated, which could therefore have induced a more pronounced inflammation process. This also corresponds with other studies [24,25]. …”
Section: Discussionmentioning
confidence: 50%
“…The chosen control was polyglactin 910, a multifilamentar copolymer of biological source made of 90% glycolide and 10% L-lactide, nonantigenic, non-pyrogenic, widely described in the literature in order to compare the histological response in the bladder wall with the results of that new material (1,2). It is indicated for the use in all but cardiovascular and neurological tissues, and is absorbable with minimal inflammatory reaction (10).…”
Section: Studied Materials (Bpca)mentioning
confidence: 99%
“…Experimental and clinical studies research the best material with less immunological reaction, low cost and low inflammatory reaction, to reduce the risk of urinary stones and fistulae. In the urinary tract, several materials present a good response: polyglactin 910, polydioxanone, simple and chrome catgut, polyglicolic acid, all of them absorbable in variable times (1)(2)(3). As an advance Vol.…”
Section: Introductionmentioning
confidence: 99%
“…In some experimental rat studies, the endurance caused by suture materials and tissue reaction were evaluated, and poliglecaprone and polydioxanone were found to be appropriate suture materials for wide-defect area repairs. In these studies, polyglactin 910 was found to create severe tissue reaction, and thus, it should be used on non-infected areas [14,15] .…”
Section: Discussionmentioning
confidence: 99%